Correlation of clinical signs and symptoms of Behçet’s disease with mean platelet volume (MPV) and red cell distribution width (RDW) - Maryam Masoumi (Orphanet Journal of Rare Diseases, 2020)
Abstract Background A strong correlation was previously found between mean platelet volume (MPV), red blood cell distribution width (RDW), and the severity of signs and symptoms in patients suffering from inflammatory and autoimmune diseases. The current study evaluated these correlations in patients with Behçet’s disease (BD) as well the relationship between MPV and RDW and disease activity score on the Iranian Behçet’s Disease Dynamic Activity Measurement (IBDDAM). Methods This cross-sectional study included 319 patients with BD for whom demographic and epidemiological data, IBDDAM scores, and duration of illness was recorded. Blood samples were then obtained and the relationships between their disease status and manifestations and their laboratory parameters were evaluated with statistical models to find possible correlations. Results Our analysis showed a significantly higher RDW in patients with BD who had ocular manifestations (p < 0.001) and oral aphthae (p = 0.004). Patients with active BD had higher RDW (p < 0.001) and MPV (p < 0.001) in comparison to those with currently inactive BD. Similarly, patients who had any type of ocular manifestation had higher RDW (p < 0.001) and MPV (p < 0.001). Regression analyses identified a statistically significant model for the effect of RDW and MPV in predicting active BD status (p < 0.001), as well as its significant relationship with active ocular manifestations (p < 0.001). Conclusion BD was found to be associated with an increase in MPV and RDW, particularly during active phases. RDW and MPV were also found to have predictive value for screening to detect BD activity and its ocular complications.